Pattern of gastrointestinal and psychosomatic symptoms across the menstrual cycle in women with inflammatory bowel disease - Erkan PARLAK; Ülkü DAĞLI; Canan ALKIM; Selçuk DİŞİBEYAZ and Bilge TUNÇ and Aysel ÜLKER and Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-